Innovative ways to screen for iron deficiency anemia (IDA) - Chandra, Dian Novita (Indonesian Nutrition Association, 2025)
Iron deficiency anemia (IDA) poses a significant public health challenge in Indonesia, contributing to 75% of anemia cases among pregnant women and 42% among children under five years. Clinical diagnosis typically relies on biomarker evaluation, including hemoglobin levels, serum iron concentration, and transferrin saturation. While diagnostic protocols emphasize specificity, population-level screening efforts prioritize sensitivity to effectively identify at-risk individuals.